1999
DOI: 10.1161/01.cir.99.20.2688
|View full text |Cite
|
Sign up to set email alerts
|

Variant Estrogen and Progesterone Receptor Messages in Human Vascular Smooth Muscle

Abstract: Variant PR and ER transcripts are extensively expressed in human vascular smooth muscle. The complex tissue-specific effects of sex hormones may be mediated by the expression of heterogeneous forms of their cognate receptors. The presence of variant ERs and PRs may be of importance in altering the physiological effects of estrogens or progestins in vascular smooth muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 32 publications
(36 reference statements)
1
37
0
Order By: Relevance
“…Progesterone action is mediated via progesterone receptors (PR), which are expressed in arterial and venous smooth muscle cells. 24 However, we previously found that PR expression in mesangial cells is near the limit of detection by reverse transcriptase-polymerase chain reaction (unpublished observation, M. Potier) suggesting that progesterone action and effects are very limited in this vascular bed. Thus, progesterone deficiency may not play an important role in the progression of glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 92%
“…Progesterone action is mediated via progesterone receptors (PR), which are expressed in arterial and venous smooth muscle cells. 24 However, we previously found that PR expression in mesangial cells is near the limit of detection by reverse transcriptase-polymerase chain reaction (unpublished observation, M. Potier) suggesting that progesterone action and effects are very limited in this vascular bed. Thus, progesterone deficiency may not play an important role in the progression of glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 92%
“…Progesterone has been recently demonstrated to enhance HLA-G expression in the JEG-3 choriocarcinoma cell line and isolated first-trimester cytotrophoblasts 14 through receptor activation followed by binding to a progesterone response element, which shares 60% homology to the wild-type mouse mammary tumor virus progesterone response element sequence. 15 Furthermore, progesterone receptors are present in human heart as well as vascular endothelial and smooth muscle cells, 24,25 indicating that these tissues are possible targets for progesterone-induced HLA-G expression. Intriguingly, our results show induction of this expression after treatment with progesterone and partial inhibition after coincubation with mifepristone in HCAEC, HAEC, and …”
Section: Discussionmentioning
confidence: 99%
“…23 It is also possible that women with abdominal obesity may have functional disturbances in their ERs, or that their arterial tissues express variant forms of ER which may have anomalous transcriptional activities and may inhibit or enhance the effect of wild-type receptors. 24 Hodges et al 24 have recently reported exon deletion variants of ERs in human vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 99%